2012
DOI: 10.1002/chem.201201716
|View full text |Cite
|
Sign up to set email alerts
|

Direct CH Functionalization of Enamides and Enecarbamates by Using Visible‐Light Photoredox Catalysis

Abstract: Direct C-H functionalization of various enamides and enecarbamates was realized through visible-light photoredox catalyzed reactions. Under the optimized conditions using [Ir(ppy)(2)(dtbbpy)PF(6)] as photocatalyst in combination with Na(2)HPO(4), enamides such as N-vinylpyrrolidinone could be easily functionalized by irradiation of the reaction mixture overnight in acetonitrile with visible light. The scope of the reaction with respect to enamide and enecarbamate substrates by using diethyl 2-bromomalonate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(82 citation statements)
references
References 116 publications
4
75
0
2
Order By: Relevance
“…Thus, in the presence of isomerizable double bonds, these processes usually lead to allylic trifluoromethylation compounds as the major or only products (see below). In this regard, the first successful examples of a vinyl-CF 3 bond formation involved a Cu(I)-catalyzed electrophilic trifluoromethylation with Togni's reagent [45] or a photocatalyzed process with CF 3 SO 2 Cl [46], but these methods were restricted to enamides as starting substrates. A more general approach was later discovered using a photoredox radical trifluoromethylation with CF 3 I, exhibiting a high functional group tolerance which also included isomerizable double bonds [47] (Scheme 5, path c).…”
Section: Trifluoromethylation Of Sp 2 Carbonmentioning
confidence: 98%
“…Thus, in the presence of isomerizable double bonds, these processes usually lead to allylic trifluoromethylation compounds as the major or only products (see below). In this regard, the first successful examples of a vinyl-CF 3 bond formation involved a Cu(I)-catalyzed electrophilic trifluoromethylation with Togni's reagent [45] or a photocatalyzed process with CF 3 SO 2 Cl [46], but these methods were restricted to enamides as starting substrates. A more general approach was later discovered using a photoredox radical trifluoromethylation with CF 3 I, exhibiting a high functional group tolerance which also included isomerizable double bonds [47] (Scheme 5, path c).…”
Section: Trifluoromethylation Of Sp 2 Carbonmentioning
confidence: 98%
“…[61] Die Photokatalyse mit sichtbarem Licht bietet einen alternativen Ansatz fürdie Arylierung von Alkenen, Alkinen und Enonen in guten Ausbeuten, aber die Reaktion ist auf aktivierte Verbindungen wie Cumarine,C hinone,S tyrole und Phenylacetylene beschränkt (Schema 19 a). [63] Im Jahr 2014 berichteten Kçnig und Mitarbeiter über den ersten con-PET-Prozess (consecutive photoinduced electronen transfer), mit dem Arylbromide und -chloride reduziert werden kçnnen. [63] Im Jahr 2014 berichteten Kçnig und Mitarbeiter über den ersten con-PET-Prozess (consecutive photoinduced electronen transfer), mit dem Arylbromide und -chloride reduziert werden kçnnen.…”
Section: )-C(sp 3 )-Bindungunclassified
“…[5] On this basis,w er easoned that arene C(sp 2 )ÀHb onds,h aving the appropriate reactivity,m ight intermolecularly trap the radical intermediates B,t hus enabling the simultaneous formation of two CÀCb onds across the alkenes and the incorporation of diverse synthetically versatile functional groups.H erein, we report an ew iron-facilitated silver-mediated radical 1,2-alkylarylation of styrenes (1)w ith a-carbonyl alkyl bromides (2), and indoles (3)f or producing alkylated indoles (Scheme 1b). [5] On this basis,w er easoned that arene C(sp 2 )ÀHb onds,h aving the appropriate reactivity,m ight intermolecularly trap the radical intermediates B,t hus enabling the simultaneous formation of two CÀCb onds across the alkenes and the incorporation of diverse synthetically versatile functional groups.H erein, we report an ew iron-facilitated silver-mediated radical 1,2-alkylarylation of styrenes (1)w ith a-carbonyl alkyl bromides (2), and indoles (3)f or producing alkylated indoles (Scheme 1b).…”
mentioning
confidence: 99%
“…Notably,a lkyl-functionalized indoles are important structural motifs in natural products and pharmaceuticals,a swell as useful intermediates in synthesis. Theresults demonstrated that silver salts are the real catalysts for the three-component reaction (entries [5][6][7][8][9]: the reaction did not proceed without the silver salts,even in the presence of abase (entries 5and 6), and al ower amount of Ag 2 CO 3 had an egative effect (entry 7). [9] Thealkene 1awas treated with 2a, 3a,[Fe(acac) 3 ], and Ag 2 CO 3 and led to the formation of the desired 1,2-alkylarylation product 4 in 83 %y ield (entry 1).…”
mentioning
confidence: 99%